Maternal opioid exposure, neonatal abstinence syndrome, and infant healthcare utilization: A retrospective cohort analysis. (1st June 2021) - Ko, Jean Y.; Yoon, Jangho; Tong, Van T.; Haight, Sarah C.; Patel, Roshni; Rockhill, Karilynn M.; Luck, Jeff; Shapiro-Mendoza, Carrie
Highlights: Little known about opioid exposed/NAS infants' healthcare utilization in 1st year of life. Infants categorized by maternal opioid exposure and NAS status. Opioid exposed and/or NAS infants more likely hospitalized within 4 weeks and 1 year. Opioid exposed and/or NAS infants more likely to have ≥2 sick visits and ≥1 ED visit. Efforts needed to mitigate future hospitalization risk and encourage use of preventative services. Abstract: Background: We sought to describe healthcare utilization of infants by maternal opioid exposure and neonatal abstinence syndrome (NAS) status. Methods: A longitudinal cohort of 81, 833 maternal-infant dyads were identified from Oregon's 2008–2012 linked birth certificate and Medicaid eligibility and claims data. Chi-square tests compared term infants (≥37 weeks of gestational age) by maternal opioid exposure, defined using International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD-9-CM ) diagnosis codes or prescription fills, and NAS, defined using ICD-9-CM codes, such that infants were categorized as Opioid+/ NAS+, Opioid+/NAS-, Opioid-/NAS+, and Opioid-/NAS-. Modified Poisson regression was used to calculate adjusted risk ratios (aRR) and 95 % confidence intervals (CI) for healthcare utilization for each infant group compared to Opioid-/NAS- infants. Results: The prevalence of documented maternal opioid exposure was 123.1 per 1000 dyads and NAS incidence was 5.8 per 1000 dyads. Compared to Opioid-/NAS- infants, infants with maternal opioid exposures were more likely to be hospitalized within 4 weeks (Opioid+/ NAS+: [aRR: 4.7; 95 % CI: 4.3–5.1]; Opioid+/ NAS-: [aRR: 3.7; 95 %CI: 3.1–4.5]) and a year after birth (Opioid+/ NAS+: [aRR: 3.7; 95 %CI: 3.4-4.0]; Opioid+/ NAS-: [aRR: 2.8; 95 %CI: 2.3–3.4]). Infants with maternal opioid exposure and/or NAS were more likely than Opioid-/NAS- infants to have ≥2 sick visits and any ED visits in the year after birth. Conclusions: Infants with NAS and/or maternal opioid exposure had greater healthcare utilization than infants without NAS or opioid exposure. Efforts to mitigate future hospitalization risk and encourage participation in preventative services within the first year of life may improve outcomes.